Proarrhythmic Remodeling of Calcium Homeostasis in Cardiac Disease; Implications for Diabetes and Obesity - Hamilton, Shanna; Terentyev, Dmitry (Frontiers in Physiology, 2018)
A rapid growth in the incidence of diabetes and obesity has transpired to a major heath issue and economic burden in the postindustrial world, with more than 29 million patients affected in the United States alone. Cardiovascular defects have been established as the leading cause of mortality and morbidity of diabetic patients. Over the last decade, significant progress has been made in delineating mechanisms responsible for the diminished cardiac contractile function and enhanced propensity for malignant cardiac arrhythmias characteristic of diabetic disease. Rhythmic cardiac contractility relies upon the precise interplay between several cellular Ca2+ transport protein complexes including plasmalemmal L-type Ca2+ channels (LTCC), Na+-Ca2+ exchanger (NCX1), Sarco/endoplasmic Reticulum (SR) Ca2+-ATPase (SERCa2a) and ryanodine receptors (RyR2s), the SR Ca2+ release channels. Here we provide an overview of changes in Ca2+ homeostasis in diabetic ventricular myocytes and discuss the therapeutic potential of targeting Ca2+ handling proteins in the prevention of diabetes-associated cardiomyopathy and arrhythmogenesis.